The X-ray Crystal Structure of Glutathionylcobalamin Revealed - Hannibal, Luciana (2010)
The first evidence of a complex between glutathione and cobalamin, glutathionylcobalamin (GSCbl), was presented by Wagner and Bernhauer more than 40 years ago (Ann N Y Acad Sci, 1964, 112, 580). More recently, NMR and EXAFS solution studies by Brown et al (Biochemistry, 1993, 32, 8421) and Scheuring et al. (Biochemistry, 1994, 33, 6310), respectively, provided evidence that the glutathionyl moiety in GSCbl is bound to the cobalt center via a Co-S bond. Despite continued efforts, the structural analysis of glutathionylcobalamin in the solid state has remained elusive. Here we report the first atomic resolution crystal structure of GSCbl, refined to a crystallographic R-factor of 0.0683. The glutathione moiety is bound to the cobalt center through the sulfur atom as expected, with a Co-S bond distance of 2.295(1) A. This distance agrees with the distance obtained from the EXAFS analysis of GSCbl (2.280(5) Å). However, the bond to the axial α-5,6-dimethylbenzimidazole base (DMB), 2.074(3) Å, is significantly shorter than that determined from the EXAFS measurements (Co-N3B = 2.15(3) Å). The corrin fold angle is 24.7°, the highest ever reported for a cobalamin structure, and points in the direction of the β-face of the corrin, towards the glutathione (GS(−)). The GS(−) ligand has been modeled in two conformations, each featuring distinct hydrogen bonding interactions. In both conformations, the α-carboxylate group of the GS(−) ligand interacts with the generally rigid side chain a of the cobalamin molecule, resulting in two distinct conformations. A comparison with the structure of other thiolatocobalamins revealed high similarity in the positions of the atoms in the cysteinyl moiety, the fold of the corrin rings, and the Co-S bond distances.